Lingkup Dunia Cyber di Indonesia - Desri Amanda Firdayani Nasution; Ria Septiana; Widya Syaputri; Nurbaiti Nurbaiti (Publikasi Indonesia, 2023)
In this day and age, technological developments are increasingly advanced, many use the internet as a tool or space to communicate with others. However, with the advancement of technology and the internet, it also not only has a positive impact, but there is also a negative side, namely that there are also many people who make threats from the internet or what is also known as Cybercrime. Cybercrime is an attack carried out through internet technology. Cyber attacks are also one of the most common attacks in the world, one of which is Indonesia. For 2022 alone, more than 700 million cyberattacks have been carried out. Based on the data obtained, this research is included in the category of qualitative research. Qualitative research is research that is basically a way to understand phenomena by obtaining data from research in the form of data or activities seen from observations. This research was conducted to test how many attacks are carried out by cyber against the world, including the country. Cybersecurity is also carried out at this stage so that data theft actions do not occur that can harm the country and others as well.